2018
DOI: 10.1002/adfm.201801685
|View full text |Cite
|
Sign up to set email alerts
|

Stretch‐Driven Increase in Ultrahigh Thermal Conductance of Hydrogenated Borophene and Dimensionality Crossover in Phonon Transmission

Abstract: Inspirited by the wide range of applications of graphene and the similarity between boron and carbon, 2D boron sheets have gained extensive research interest. In this work, using first-principles combined with a nonequilibrium Green's function method, thermal conductance of fully hydrogenated borophene, named borophane, is studied. Interestingly and in contrast to widely perceived sense, at 300 K, it is found that the thermal conductance of borophane in the armchair direction is remarkably larger than that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 62 publications
(71 reference statements)
0
45
0
Order By: Relevance
“…We further tested the bandwidth of the as‐built MZI device with a sine wave‐type pump (see Figure S1, Supporting Information), which indicates a response time limit of ≈0.41 ms, being well consistent with above results. The superior photo‐thermal response might be attributed to the lower mass of boron atom, which, combined with the high stiffness of lattice structure, gives higher electron‐phonon coupling and thus higher phonon velocities, implying more efficient thermal transport . The detailed mechanism, however, deserves further investigations.…”
Section: Comparison Of Different 2d Materials‐based Similar Devicesmentioning
confidence: 99%
“…We further tested the bandwidth of the as‐built MZI device with a sine wave‐type pump (see Figure S1, Supporting Information), which indicates a response time limit of ≈0.41 ms, being well consistent with above results. The superior photo‐thermal response might be attributed to the lower mass of boron atom, which, combined with the high stiffness of lattice structure, gives higher electron‐phonon coupling and thus higher phonon velocities, implying more efficient thermal transport . The detailed mechanism, however, deserves further investigations.…”
Section: Comparison Of Different 2d Materials‐based Similar Devicesmentioning
confidence: 99%
“…Recently, 2D materials have triggered a large number of interest due to the striking physical properties related to the low dimensionality. [1][2][3] Graphene 1 in group-IV, borophene in group-III 4,5 and black phosphorous in group-V 6,7 have been extensively investigated experimentally and theoretically. However, researches related to group-VI monolayer materials are still lacking to date.…”
Section: Introductionmentioning
confidence: 99%
“…Borophene shows high in‐plane stiffness and off‐plane flexibility. Attributed to the strong B‐B bond, high atomic density, and unique phonon dispersion relationship, the thermal conductance of borophene and hydrogenated borophene (i.e., borophane) can be even higher than that of graphene . More interesting, based on first‐principles calculations, Li et al found that the experimentally fabricated borophene sheet can form stable nanotube structure after hydrogenation, denoted as H‐BNTs.…”
Section: Introductionmentioning
confidence: 99%